Anatomic Reconstruction of the Medial Patellofemoral Ligament in Children and Adolescents With Open Growth Plates: Surgical Technique and Clinical Outcome. (January 2013) - Nelitz, Manfred; Dreyhaupt, Jens; Reichel, Heiko; Woelfle, Julia; Lippacher, Sabine
Background: Recurrent lateral patellar dislocation is a common knee injury in the skeletally immature adolescent. Because of the open physis, operative therapy in children is challenging. This study presents the outcomes of a minimally invasive technique for anatomic reconstruction of the medial patellofemoral ligament (MPFL) in children that respects the distal femoral physis. Hypothesis: Anatomic reconstruction of the MPFL in children that maintains the distal femoral physis will prevent redislocation, preserve the distal femoral physis, and improve knee function. Study Design: Case series; Level of evidence, 4. Methods: Twenty-one consecutive patients with patellofemoral instability and open growth plates underwent anatomic reconstruction of the MPFL that maintained the distal femoral growth plate. Preoperative radiographic examination included AP and lateral views to assess patella alta and limb alignment. Magnetic resonance imaging was performed to evaluate trochlear dysplasia and tibial tubercle–trochlear groove (TT-TG) distance. Evaluation included preoperative and postoperative physical examination, Kujala score, and Tegner activity score. Results: The average age at the time of operation was 12.2 years (range, 10.3-13.9). The average follow-up after operation was 2.8 years after surgery (range, 2.0-3.6). No recurrent dislocation occurred, but 2 patients with high-grade trochlear dysplasia still had a positive apprehension sign. The Kujala score significantly improved from 72.9 (range, 37-87) preoperatively to 92.8 (range, 74-100) postoperatively ( P < .01). The Tegner activity score decreased, but not significantly, from 6.0 (range, 3-9) preoperatively to 5.8 (range, 3-9) postoperatively ( P = .48). Conclusion: Anatomic reconstruction of the MPFL that respects the distal femoral physis in skeletally immature patients is a safe and effective technique for the treatment of patellofemoral instability and allows patients to return to sports without redislocation of the patella.